Dietary postbiotic Lactobacillus plantarum improves serum and ruminal antioxidant activity and upregulates hepatic antioxidant enzymes and ruminal barrier function in post-weaning lambs - Wan Ibrahim, Wan Ahmad Izuddin; Humam, Ali Merzza; Loh, Teck Chwen; Foo, Hooi Ling; Samsudin, Anjas Asmara @ Ab Hadi (MDPI, 2020)
Postbiotics from Lactobacillus plantarum have been reported to improve growth performance, nutrient utilization, immune status and gut health in livestock. However, there is scarce information on the antioxidant activity of postbiotics and its modulation of antioxidant activity and rumen barrier function in animals. We investigated the antioxidant activity of postbiotics from L. plantarum RG14, RG11 and TL1 and dietary effects in post-weaning lambs on serum and ruminal antioxidant activity, hepatic antioxidant enzymes and ruminal barrier function. Postbiotic RG14 showed the highest antioxidant activity in both 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay and was chosen to be evaluated in animal trials. Twelve post-weaning Dorper lambs were allotted to the control group and postbiotic group (0.9% (v/w) postbiotic RG14). The improvement in antioxidant activity of the postbiotic group was observed by greater glutathione peroxidase (GPX) in serum and ruminal fluid and lower serum TBARS. The findings were strengthened by the upregulation of hepatic GPX1, GPX4 and copper, zinc superoxide dismutase (Cu/Zn SOD) in the postbiotic group. Lambs received postbiotics had higher regulation of rumen barrier function through upregulation of tight junction protein (TJP), occludin (OCLD), claudin-1 (CLDN1) and CLDN4. The current study demonstrated that dietary postbiotics enhanced the serum and ruminal fluid antioxidant activity, reduced the serum lipid peroxidation and upregulated hepatic antioxidant enzymes and ruminal barrier function.